2014
DOI: 10.1111/ijfs.12475
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enzymatic hydrolysis on the biological properties of Oenothera biennis,Borago officinalis and Nigella sativa seedcake by‐products from oil pressing

Abstract: The biological properties of ethanolic (50%, v/v) extracts from Oenothera biennis, Borago officinalis, Nigella sativa seedcake before and after enzymatic hydrolysis by alpha-amylase (EC 3.2.1.1) from Aspergillus oryzae, beta-glucosidase (EC 3.2.1.21) and beta-glucanase (EC 3.2.1.6) from Aspergillus niger combinations in a ratio of 1:1:1 were investigated. Total phenolic, flavonoid and reducing sugar content for O. biennis extract after enzymatic hydrolysis was, respectively, 0.5, 1.5 and 2 times higher in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Data represent the mean values±standard deviation of six independent experiments, each performed in triplicate. Student's t-test: p<0.05. enzymatic hydrolysis on the antioxidant properties of O. biennis, B. officinalis and N. sativa seedcakes (6,14). The present study confirms that the seedcake extracts have strong antioxidant activity and the hydrolysis of glycosidic forms of polyphenols affect on the growth of their antiradical capacity.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Data represent the mean values±standard deviation of six independent experiments, each performed in triplicate. Student's t-test: p<0.05. enzymatic hydrolysis on the antioxidant properties of O. biennis, B. officinalis and N. sativa seedcakes (6,14). The present study confirms that the seedcake extracts have strong antioxidant activity and the hydrolysis of glycosidic forms of polyphenols affect on the growth of their antiradical capacity.…”
Section: Resultssupporting
confidence: 76%
“…Al-Ghazal (35) observed that the methanolic extracts of C. pepo fruitcortex have antimicrobial activity against S. aureus and E. coli, respectively whereas the aquous extract was effective against S. aureus only. In our previous studies O. biennis, B. ocinalis and N. sativa seedcake extracts before and after hydrolysis showed weak inhibition growth against bacteria and yeast, but the hydrolysis did not improve the antimicrobial properties in all tested cases (14). In the present study we observed the highest antimicrobial activity of all tested extracts after enzymatic hydrolysis of seedcakes with enzyme combination in a ratio of 1:1:1.…”
Section: Resultssupporting
confidence: 45%
See 3 more Smart Citations